Effect of initial body weight and body composition of TETRA SL laying hens on the changes in their liveweight, body fat content, egg production and egg composition during the first egg-laying period - Milisits, Gábor; Szentirmai, Eszter; Donkó, Tamás; Budai, Zoltán; Ujvári, Jolán; Áprily, Szilvia; Bajzik, Gábor; Sütő, Zoltán (Acta Agraria Kaposváriensis, 2016)
The experiment was carried out with 45 TETRA SL laying hens, which were divided into three groups based on their liveweight on the one hand and based on their body fat content (determined by means of computer tomography) on the other hand measured both at 20 weeks of age. The average liveweight of the hens in the "low liveweight"Â group was 1534Â±87g (n=14), in the "medium liveweight"Â group 1696Â±33g (n=16) and in the "high liveweight"Â group 1861Â±94g (n=15). The average fat index calculated from the CT images was 22.9Â±0.9 (n=15) in the "low fatty"Â group, 24.9Â±0.4 (n=14) in the "medium fatty"Â group and 27.2Â±1.6 (n=16) in the "high fatty"Â group. The liveweight of the experimental birds was recorded at 32, 52 and 72 weeks of age during the first egg-laying period. At the same ages the body fat content of the hens was also determined by means of computer tomography in vivo. Eggs, which were produced by the experimental birds one day before the CT examinations, were collected and, after breaking them, their yolk and albumen was separated, weighed and their ratio to the egg weight was calculated. The dry matter, crude protein and crude fat content of the eggs were analyzed chemically. Based on the results it was established that the initial body weight of the hens affected changes in the liveweight, while the initial body fat content of the hens affected changes in the body fat content significantly (P<0.05) during the whole experimental period. The low initial body weight and the high initial body fat content of the hens resulted in the lowest egg production intensity at 52 and 72 weeks of age. Neither the initial body weight nor the initial body fat content of the hens affected the chemical composition of the eggs significantly (P>0.05).